PRELIMINARY STUDY OF FLOATING OFFSHORE WIND TURBINES MOTIONS USING THE SMOOTHED PARTICLE HYDRODYNAMICS METHOD - Tagliafierro B.; Karimirad M.; Martinez-Estevez I.; Dominguez J. M.; Crespo A. J. C.; Gomez-Gesteira M.; Viccione G. (Volume 5A: Ocean Engineering, 2022)
The open-source code DualSPHysics, based on the Smoothed Particle Hydrodynamics (SPH) method for solving fluid mechanics problems, defines a complete numerical environment for simulating the interaction of floating structures with waves and currents, and includes external libraries to simulate kinematic- and dynamic-type restrictions. In this work, we propose a full validation of the presented SPH framework using validation data available for an experimental test campaign on a 1:37th-scale FOWT TLP. The first set of validation cases includes a surge decay test, to assess the quality of the fluid-solid interaction, and regular wave tests, which stimulate the mooring system to a large extent. During this phase, tendons (tension legs) that are simulated by MoorDyn+ are validated. Secondly, the numerical model has proven to predict with a high degree of accuracy the response of the investigated TLP under regular waves. Spectral comparison shows that the model is able to capture the surge and pitch dynamic amplification that occurs around the resonant fundamental mode of vibration.